Management Information System Success Rate on Pusri Palembang Hospital Using HOT-FIT Models - Dini Ken Rifarsih; Fenny Purwani; Dian Hafidh Zulfikar (Universitas Bina Darma, 2022)
Pusri Palembang Hospital is a public hospital that has implemented a Hospital Management Information System (SIMRS) since 2012. SIMRS supports all health care business processes and administrative procedures to obtain information quickly, precisely, and accurately. During the implementation of SIMRS, some obstacles often occur in its use, such as user complaints regarding the operational functions of the system so that it has not run optimally. This study aims to evaluate the success of implementing SIMRS at the Pusri Hospital in Palembang and determine the effect between variables. This study uses the HOT-Fit model variable consisting of human components (system use and user satisfaction), organization (organizational structure and environment), technology (system quality, information quality, service quality), and benefits. This study uses a survey research type with qualitative methods. Based on the analytical approach, this research is classified into quantitative research. It was preceded by quantitative research with 165 respondents and followed by qualitative research by interviewing six informants. The data analysis technique used is PLS-SEM with SmartPLS tools. The results showed that on the technology component: the quality of the system (73.0%) was good, the quality of information (74.2%) of the data produced was accurate, quality, and relevant, and the quality of service (75.5%) was good. The human component: the use of the system (74.2%) is good because the officers receive the system well, and user satisfaction (75.6%) is satisfied using SIMRS. Organizational Components: organizational structure (78.0%) and organizational environment (73.6%) are suitable. In terms of benefits (76.1%), it has helped increase efficiency and effectiveness in work. Based on the results of hypothesis testing in path analysis, it is known that there are eight relationships between variables that have a significant effect and four relationships that do not have a significant effect. The most significant influence is the influence of the organizational structure on the organizational environment. At the same time, the lowest level of correlation is the relationship between the quality of information and the use of the system. The overall success rate of SIMRS implementation is 76.1%. The research results show that the existence of the system helps users support their work and the successful use of the system from the user's perception at this time is at a successful level.